Identifikasi Senyawa Marker Dominan Ekstrak Daun Sirih Hitam dan Kuantifikasi Berdasarkan Perbedaan Lokasi Tanam: Identification of Dominant Marker Compounds of Black Betel Leaf Extract and Quantification Based on Differences in Planting Locations - Fajar Prasetya; M Arifuddin; Arsyik Ibrahim (Jurnal Sains dan Kesehatan, 2021)
It has been revealed that the benefits of black betel leaf extract have created an opportunity for the black betel plant to be commercialized. The several benefits of black betel leaf extract are antimicrobial, anti-inflammatory, cytotoxic, and antioxidant. The extraction method uses maceration techniques. Identification of active markers as antimicrobials (Streptococcus mutans, Streptococcus sanguinis, Candida albicans) begins with Bioautography Thin Layer Chromatography (TLC), for isolation from macerated extracts followed by Vacuum Liquid Chromatography Fractionation (KCV), conventional Column Subfraction (KK), Layer Chromatography Thin Preparative (TLC). Quantification of marker compounds using a Thin Layer Chromatography (TLC) Scanner. Samples of black betel leaf (P. betle L. var Nigra) were collected from Samarinda (East Kalimantan), Wonosobo (Central Java), Godean (Yogyakarta), Banyuwangi (East Java) in June 2020. The results of the TLC test for bioautography of 70% ethanol extract and the ethanol fraction of 96% black betel leaf showed that the active spot of ethanol extract 70% for antibacterial activity on Streptococcus mutans Atcc 25175 and Streptococcus sanguinis Atcc 10556 was Rf 0.729 cm, the active spot of the ethanol fraction 96% for the activity of the fungus Candida albicans ATTC 10231; Rf 0.486 cm. Purification using TLC multi eluent with eluent I Hexane: Ethyl Acetate (7: 3) as non polar eluent and eluent II Chloroform: Ethyl Acetate (4: 1) as polar eluent on different TLC plates. The results obtained in the form of a single stain with Rf = 0.4 in eluent I and Rf = 0.73 in eluent II. The results of measuring the levels of the dominant marker compound using a TLC scanner showed that the highest marker compound area was from betel leaf grown in the Godean area (Yogyakarta) with the number 29869.4.